2010
DOI: 10.1038/sj.bjc.6605992
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of ANXA6, HSP27, PRDX2, NCF2, and TPM4 during uterine cervix carcinogenesis: diagnostic and prognostic value

Abstract: Background:Cytology-based diagnostics of squamous cervical cancer (SCC) precursor lesions is subjective and can be improved by objective markers.Methods:IHC-based analysis of ANXA6, HSP27, peroxiredoxin 2 (PRDX2), NCF2, and tropomyosin 4 (TPM4) during SCC carcinogenesis.Results:Expression of ANXA6, HSP27, PRDX2, and NCF2 in the cytoplasm of dysplastic cells increased from cervical intraepithelial neoplasia 2/3 (CIN2/3) to microinvasive cancer. Invasive SCC showed lower expression of TPM4 than CIN and normal ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 42 publications
1
54
1
1
Order By: Relevance
“…To our knowledge, this is the first study to evaluate HSPB1 expression in human bronchial epithelium carcinogenic process and its early diagnostic significance in LSCC. Interestingly, previous studies have showed that HSPB1 was overexpressed in preneoplastic lesions in the uterine cervix and gastric cancer, and has an early diagnostic significance for these two tumors (56,57), which also supports HSPB1 as biomarker for early detection of LSCC. It has been reported that HSPB1 overexpression was involved in liver carcinogenesis induced by chemical carcinogens (58), and HSPB1 expression in benign proliferating breast lesions increased risk of cell malignant progression (59).…”
Section: Knockdown Of Gstp1 Increased the Susceptibility Of Human Bromentioning
confidence: 83%
“…To our knowledge, this is the first study to evaluate HSPB1 expression in human bronchial epithelium carcinogenic process and its early diagnostic significance in LSCC. Interestingly, previous studies have showed that HSPB1 was overexpressed in preneoplastic lesions in the uterine cervix and gastric cancer, and has an early diagnostic significance for these two tumors (56,57), which also supports HSPB1 as biomarker for early detection of LSCC. It has been reported that HSPB1 overexpression was involved in liver carcinogenesis induced by chemical carcinogens (58), and HSPB1 expression in benign proliferating breast lesions increased risk of cell malignant progression (59).…”
Section: Knockdown Of Gstp1 Increased the Susceptibility Of Human Bromentioning
confidence: 83%
“…+ cells among atypical cells increased from CIN2/3 to invasive SCC (40). Based on these results, it is possible to hypothesize that the detectable alterations in the protein expression levels of AnxA6 in SCC precursor lesions may aid in the cytological and pathological diagnostics of CC and its prognostic evaluation.…”
Section: Roles Of Anxa6 In Cervical Cancer Progression and Malignancymentioning
confidence: 92%
“…In addition, strong expression of AnxA6 was observed in the nucleus of SCC cells, compared with the weak or moderate expression observed in the cytoplasm of SCE cells (25). However, these may be infiltrating immune cells, since their histopathological appearance was observed to be variable (40). Another study by Lomnytska et al (40) indicated that AnxA6 may aid cytology-based diagnostics of SCC precursor lesions, since its expression levels vary during the different sequential steps of SCC carcinogenesis.…”
Section: Roles Of Anxa6 In Cervical Cancer Progression and Malignancymentioning
confidence: 99%
See 2 more Smart Citations